Cancer stemness : unravelling the molecular mechanisms controlling stem cell differentiation and self-renewal - Heffron, Cynthia Constance Bridgette Beatrice (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Histopathology & Morbid Anatomy, 2009)
Understanding the molecular mechanisms behind cancer cell proliferation and regulation is the key to discovering potential future successful therapies for cancer. The World Health Organisation estimates that 7.6 million people died from cancer in 2005 with that number expected to reach 9 million in 2015 and 11.5 million in 2030. The concept of a cancer stem cell as the core cancer initiating agent within a tumour has come to the forefront of tumour biology with a cancer stem cell population identified in many different tumour types including prostate, breast, skin, colon and ovarian cancer. Cancer stem cells and normal stem cells share two fundamental properties, namely the ability to self-renew and the ability to differentiate. The characterisation of the molecular mechanisms underlying these two processes will be vital to the understanding of the regulation of cancer cell proliferation and progression. The specific targeting of cancer stem cells within a tumour as a treatment modality may provide more effective cancer treatment in the future as many current treatments are not eliminating the small but significant population of cancer stem cells that result in metastasis and recurrence. Teratocarcinomas are malignant germ cell tumours that occur in the testes and ovary and are considered to be the classical stem cell tumour being composed of an undifferentiated population of embryonal carcinoma cells and mature differentiated tissues. This tumour’s ability to differentiate as well as being inherently malignant makes teratoma tumourigenesis an ideal model to study the concept of cancer sternness and thus identify stem cell markers and targets that may be useful in the assessment and treatment of cancer stem cells in many other tumours.
Keywords: Histopathology and Morbid Anatomy, Ph.D.; Ph.D. Trinity College Dublin